RESPONSE TO TEMPERATURE IN THE OXYGEN-UPTAKE OF AWAKE AND DORMANT FROGS (AMPHIBIA, LEPTODACTYLIDAE) - Abe, Augusto Shinya [UNESP]; Garcia, L. S. (Swets Zeitlinger Publishers, 1991)
In southeastern Brazil the leptodactylid frogs Leptodactylus fuscus and Physalaemus fuscomaculatus enter dormancy during the dry season. Oxygen uptake was measured in awake and dormant groups of both species in a temperature range at which these frogs are usually exposed throughout the year. Oxygen uptake was lower for dormant groups at high temperature, and a lack of response to temperature was reported between 20 - 25 C in the dormant group of both species. This temperature-intensitive range can be considered an adaptive feature to save fat reserves during dormancy.